2004
DOI: 10.1128/iai.72.2.1195-1198.2004
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Five Outer Membrane-Associated Proteins among Cross-Protective Factor Proteins ofPasteurella multocida

Abstract: Fowl cholera is caused by Pasteurella multocida serovars A:1, A:3, and A:4. The 39-kDa cross-protective factor protein and four other membrane proteins of the membrane proteome of P. multocida were identified. We determined that the 39-kDa cross-protective protein was Pasteurella lipoprotein B, or PlpB

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 13 publications
1
22
0
Order By: Relevance
“…However, the protective antigen was later identifi ed erroneously as the lipoprotein PlpB (Tabatabai and Zehr 2004 ), which shows similarity to methionine -binding proteins from many other bacterial species. In fact, the cross -protective antigen is PlpE, a lipoprotein with homologs in Mannheimia haemolytica and Actinobacillus pleuropneumoniae that stimulate protective immunity in cattle and pigs (Wu et al 2007 ).…”
Section: Individual Antigensmentioning
confidence: 99%
“…However, the protective antigen was later identifi ed erroneously as the lipoprotein PlpB (Tabatabai and Zehr 2004 ), which shows similarity to methionine -binding proteins from many other bacterial species. In fact, the cross -protective antigen is PlpE, a lipoprotein with homologs in Mannheimia haemolytica and Actinobacillus pleuropneumoniae that stimulate protective immunity in cattle and pigs (Wu et al 2007 ).…”
Section: Individual Antigensmentioning
confidence: 99%
“…Recently, Wu and colleagues reported that mice immunized with recombinant PlpB protein were not protected against challenge infection with 30 or 60 CFU of P. multocida X-73 serotype A:1 [14]. However, it was unclear whether or not the derived recombinant PlpB was the same protein as the 39 kDa protein that was cross-protective as described earlier by Rimler and Tobatabai [10,12]. Tobatabai and Zehr reported that the PlpB protein was a 30-kDa protein that appeared on the SDS gel at 39 kDa [12].…”
Section: Discussionmentioning
confidence: 93%
“…However, it was unclear whether or not the derived recombinant PlpB was the same protein as the 39 kDa protein that was cross-protective as described earlier by Rimler and Tobatabai [10,12]. Tobatabai and Zehr reported that the PlpB protein was a 30-kDa protein that appeared on the SDS gel at 39 kDa [12]. Nevertheless, Wu et al reported the PlpB protein with molecular mass of only 28 kDa and finally concluded that this PlpB was not the same protein as the reported 39-kDa cross protective protein [14].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations